MORPHOLOGY OF PTERYGIUM - Rajabov Hamid (Scholar Express Journals, 2023)
This article details pterygium: epidemiology, prevention and treatment, risk factors and pathogenesis, pterygium excision, post-operative management, conjunctival grafting, indication for surgery, pterygium morphology
Keywords: pterygium; morphology; pathogenesis; epidemiology